Influence of abiotic factors on invasive behaviour of alien species Elodea nuttallii in the Drava River (Slovenia). Issue 1 (18th November 2013) - Grudnik, Zdenka Mazej; Jelenko, Ida; Germ, Mateja
<x content-type="archive" xml:space="preserve">Abstract</x> The alien and potentially invasive species Elodea nuttallii was observed for the first time in Slovenia's Drava River in 2007, when its huge biomasses were observed at some locations. Changes in biomass of submerged macrophyte communities and abiotic factors such as water temperature, discharge and level were monitored at two impoundments of the Drava River (2009, 2010 and 2011). The correlations between abiotic factors and developed final biomass were assessed to determine if the level of abiotic factors has an impact on the final biomass and invasive behaviour of E. nuttallii. The results obtained showed that biomass of E. nuttallii was not excessive in 2009 and 2010, while in the year 2011 it developed huge biomass at locations, which were not directly exposed to the main water current. The biomass of Myriophyllum spicatum was also higher in 2011 in comparison with 2009 and 2010 but not in such high degree. The key factor for the development of the final biomass of E. nuttallii was the water temperatures in winter and spring and also the point at which water temperatures in spring surpassed 10°C. The invasive behaviour of E. nuttallii is expected in the years with higher temperatures in January and March and at the locations which are not directly exposed to the main water current. We assume that continuation of the deposition of silt in the impoundments of the Drava River could contribute to invasive behaviour of species E. nuttallii in the years with mild winters and warmer springs.